Population Dynamics of Reba Carp Cirrhinus Reba From Indus River, Sukkur, Sindh, Pakistan (Bangladesh Journal of Zoology, 2020)
Present work was done from Indus River, Sukkur, Sindh, Pakistan to evaluate the present stock of Cirrhinus reba Suhni (Reba carp) for first time. Since the assessment of stocks deliver the important knowledge of stocks of commercially important fish species to the fisheries managers to make better strategic plans for sustainable exploitation. Data based on length-frequency was obtained from October 2015 to March 2016, a total of 463 pairs of length-weight were measured. Minimum length was measured to 13cm, maximum length was 29cm and the average length of 17cm was measured with minimum weight of 15g, maximum weight of224g and67g was the average weight. Obtained results of length-weight relationship were R2 = 0.817, a = 0.037 and b = 2.557. Growth parameters were computed as L∞= 29.40 cm and= 0.240 year-1using ELEFAN method in FISAT computer package. Growth performance index (∅′) was calculated as ∅′ = 2.317 year-1 Total mortality Z, natural mortality M and fishing mortality F was estimated as= 0.630 year-1, M= 0.617 year-1 and F=0.012 year-1 respectively. Using (E = F/Z) the exploitation ratio was obtained as E=0.019 year-1 Current fishing mortality rate of 0.012 was smaller than the target biological reference points (Fopt) of M (0.617). While MSY was recorded as; 8.144 tonsyear-1 which showed the higher results than 0.031 tons year-1ofcurrent catch. This study concluded that the C. reba confronting poor health though the stocks found not to be overexploited in the region.Bangladesh J. Zool. 48(1): 81-91, 2020